Characterisation of Colistin -Resistant Enterobacterales and Acinetobacter Strains Carrying mcr Genes from Asian Aquaculture Products - Kalová, Alžběta; Gelbíčová, Tereza; Overballe-Petersen, Søren; Litrup, Eva; Karpíšková, Renáta (Antibiotics (Basel, Switzerland), 2021)
Aquaculture systems are widely recognised as hotspots for horizontal gene transfer, and the need for screening for bacteria carrying antimicrobial resistance genes in aquaculture systems is becoming more important. In this study, we characterised seventeen bacterial strains (Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, and A. nosocomialis) resistant to colistin originating from retailed aquaculture products imported from Vietnam to the Czech Republic. The mcr-1.1 gene was found located on plasmid types IncHI2, IncI2, and IncX4, as well as on the rarely described plasmid types IncFIB-FIC and IncFIB(K), phage-like plasmid p0111, and on the chromosome of E. coli. One E. coli strain carried the mcr-3.5 gene on IncFII(pCoo) plasmid in addition to the mcr-1.1 gene located on IncHI2 plasmid. K. pneumoniae was found to carry the mcr-1.1 and mcr-8.2 genes on IncFIA(HI1) plasmid. The mcr-4.3 gene was found on similar untypeable plasmids of A. baumannii and A. nosocomialis strains, pointing to the possible interspecies transfer of plasmids carrying the mcr-4 gene. Our results highlight that some aquaculture products of Asian origin can represent an important source of variable plasmids carrying mcr genes. The results showed an involvement of phages in the incorporation of the mcr-1 gene into plasmids or the chromosome in E. coli strains from aquaculture. The detection of E. coli with the mcr-1 gene in the chromosome points to the risks associated with the stabilisation of the mcr genes in the bacterial chromosome.
Keywords: colistin; resistance; plasmids; mcr genes